Heterogeneity of Candida bloodstream isolates in an academic medical center and affiliated hospitals - Nancy E. Scott; Elizabeth Wash; Christopher Zajac; Serin E. Erayil; Susan E. Kline; Anna Selmecki (Microbiology Spectrum)
ABSTRACT Invasive Candida bloodstream infections (candidemia) are a deadly global health threat. Rare Candida species are becoming increasingly important causes of candidemia. Phenotypic data, including patterns of antifungal drug resistance, are limited. There is a geographic variation in the distribution of Candida species and frequency of antifungal drug resistance, meaning that regional data can have significant clinical value. Here, we report on the species distribution, frequency of antifungal drug resistance, and phenotypic variability of Candida bloodstream isolates from an academic medical center and five affiliated hospitals in the Minneapolis-Saint Paul region of Minnesota collected during an 18-month period from 2019 to 2021. We collected 288 isolates spanning 11 species from 119 patients. C. albicans was recovered from 45% of cases, followed by C. glabrata (35%), C. parapsilosis (7%), and C. tropicalis (2.5%), with 10% of cases representing additional rare species. We performed antifungal drug susceptibility by the EUCAST (European Committee on Antimicrobial Susceptibility Testing) method for three major drug classes. Concerningly, we identified fluconazole, micafungin, and multidrug resistance rates in C. glabrata that were ~2 times higher than that reported in other regions of the United States. Through analysis of serial isolates from individual patients, we identified clinically relevant within-patient differences of MIC values in multiple drug classes. We also report phenotypic data in rare non-albicans Candida species to address a significant gap in available data. Our results provide valuable clinical data relevant to antifungal stewardship efforts and highlight important areas of future research, including within-patient dynamics of infection and the mechanisms of drug resistance in rare Candida species.IMPORTANCECandida species are an important cause of hospital-acquired infection. The prevalence of species causing infections and the frequency of antifungal drug resistance have changed over time. Reporting the regional Candida species distribution and phenotypes has clinical significance. Current clinical microbiology practices may underestimate the within-host diversity of infecting strains, including important variation in drug susceptibility. Our study reports the results of an 18-month survey of Candida bloodstream infections in an academic medical center and associated hospitals in the Minneapolis-Saint Paul region of Minnesota. We identified antifungal drug resistance, including multidrug resistance, in multiple non-albicans species. By analyzing serial isolates from individual patients, we identified clinically relevant differences in drug susceptibility during infection. Our results contribute data to antifungal stewardship efforts and identify avenues of future research.